Inverse nodal problem for p-Laplacian Bessel equation with polynomially dependent spectral parameter - Gulsen, Tuba; Yilmaz, Emrah; Hamadamen, Mudhafar (De Gruyter Poland Sp Zoo, 2018)
In this study, solution of inverse nodal problem for p-Laplacian Bessel equation is extended to the case that boundary condition depends on polynomial eigenparameter. To find spectral datas as eigenvalues and nodal parameters of this problem, we used a modified Prfifer substitution. Then, reconstruction formula of the potential functions is also obtained by using nodal lenghts. However, this method is similar to used in [Koyunbakan H., Inverse nodal problem for p-Laplacian energy-dependent Sturm-Liouville equation, Bound. Value Probl., 2013, 2013:272,1-8], our results are more general.
Keywords: inverse nodal problem; Prufer substitution; p-Laplacian Bessel equation